Food Waste at Consumer Level A Comprehensive Literature Review - Principato, Ludovica (SpringerBriefs in Environmental Science,, 2018)
This book presents what is the state-of-the-art in the field of the food waste phenomenon at consumer level, including a thorough literature review, and it highlights trends in the field. It provides a comprehensive starting point for future research. Food waste represents a major public policy issue, which is included in the UN Sustainable Development Goals. In this context, the present work identifies the most important definitions given to food waste and its environmental, social and economic impacts. With a comprehensive literature review that covers a forty-year time span (1977-2017), this book highlights the multiple, complex facets of food waste at the consumer level. Drawing from behavioural and marketing theories, it proposes a new theoretical framework with the aim to better explain food waste behaviour. Extensive research is being carried out on the main worldwide initiatives (both public and private) and food policies aimed at tackling the phenomenon. .